Strengths and Limitations of SmallTalk2Me App in English Language Proficiency Evaluation - Laras Ayuningtyas Manggiasih; Yurike Risa Loreana; Abidatul Azizah; Nunung Nurjati (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2023)
This paper explores the strengths and limitations of the SmallTalk2Me App, an AI-driven language assessment tool, in evaluating English language proficiency. The study adopts a mixed-method approach, combining interviews with three experienced English teachers and a comprehensive literature review to provide a comprehensive analysis of the app's performance. The research begins with an exploration of the app's strengths, which include its objective and consistent evaluation metrics. The app's automated nature ensures that all test takers are assessed based on the same predefined criteria, reducing human bias and enhancing the reliability of evaluations. Also, it offers immediate feedback, allowing learners to identify their areas of improvement promptly and adapt their learning strategies accordingly. Conversely, the limitations of the SmallTalk2Me App are also discussed. One notable limitation is the challenge of replicating the complexity of real-life communication contexts. App-based assessments may not fully capture the intricacies of natural conversations. Additionally, the app's pronunciation assessment may struggle with accurately recognizing variations in accents and speech patterns, leading to potential inaccuracies in pronunciation evaluation. The insights from the interviews and literature review contribute to a comprehensive understanding of the app's performance, offering valuable implications for its effective use in language teaching and learning settings.